Syawir dan Penguatan Public Speaking Santri (Studi di Madrasah Diniyah Al-Amiriyyah Pondok Pesantren Darussalam Blokagung Banyuwangi) - Afif Mahmudi; Hasyim Iskandar; Moh. Muslimin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to analyze the implementation of syawir activities and their role in improving students’ public speaking skills at Madrasah Diniyah Al-Amiriyyah, Darussalam Islamic Boarding School, Blokagung Banyuwangi. This research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Informants were selected purposively, consisting of MUFADA administrators, pesantren authorities, and students at the Wustho and Ulya levels. Data were analyzed using the Miles and Huberman model with validity tested through triangulation. The results show that syawir is conducted regularly and systematically through several forms, including daily sessions, Monday night sessions, Thursday night sessions, and monthly syawir kubro. These activities involve scientific discussions based on classical Islamic texts, encouraging students to actively express opinions and construct arguments. The findings indicate that syawir plays a significant role in enhancing students’ public speaking skills, as reflected in increased confidence, more structured speech delivery, and sharper analytical ability. Despite challenges such as fatigue and boredom, syawir remains an effective participatory learning model that integrates intellectual development with communication skill enhancement.